2020
DOI: 10.1002/syst.202000013
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous Aminolytic Cyclization and Self‐Assembly of Dipeptide Methyl Esters in Water

Abstract: Dipeptides are known to spontaneously cyclize to diketopiperazines, and in some cases these cyclic dipeptides have been shown to self‐assemble to form supramolecular nanostructures. Herein, we demonstrate the in situ cyclization of dipeptide methyl esters in aqueous buffer by intramolecular aminolysis, leading to the formation of diverse supramolecular nanostructures. The chemical nature of the amino acid side chains dictates the supramolecular arrangement and resulting nanoscale architectures. For c[LF], supr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Recently, the spontaneous cyclization and self-assembly of dipeptide methyl esters was reported, where the intramolecular aminolysis leads to the formation of cyclic self-assembled structures in aqueous media. 168 The obtained morphologies were found to be sequence-specific, e.g., the dipeptide LF-OMe yields c(LF) fibers that result in gelation, whereas the sequence LL-OMe assembles into tapes and the dipeptide DF-OMe forms spherical aggregates. It was found that cooperative assembly of c(LF) and the metalloporphyrin Fe III -TMPyP produced nanofibers that catalyze the oxidation of organic phenol in water.…”
Section: Catalysis and Reactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the spontaneous cyclization and self-assembly of dipeptide methyl esters was reported, where the intramolecular aminolysis leads to the formation of cyclic self-assembled structures in aqueous media. 168 The obtained morphologies were found to be sequence-specific, e.g., the dipeptide LF-OMe yields c(LF) fibers that result in gelation, whereas the sequence LL-OMe assembles into tapes and the dipeptide DF-OMe forms spherical aggregates. It was found that cooperative assembly of c(LF) and the metalloporphyrin Fe III -TMPyP produced nanofibers that catalyze the oxidation of organic phenol in water.…”
Section: Catalysis and Reactivitymentioning
confidence: 99%
“…Scale bars, 500 nm; z -scales for the AFM images, −18.9 to 23.6 nm and −50 to 50 nm, respectively. (A,B) Reproduced with permission from ref . Copyright 2020 Springer Nature.…”
Section: Structures In and Out Of Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…Short peptides and their analogues have been attracting great interest in recent years as building blocks for soft matter. [1][2][3][4][5][6][7] They offer several advantages over other molecular classes, such as ease of preparation and scale-up, low cost, inherent biocompatibility and biodegradability, as well as the possibility to encode biological messages. 8 In particular, it has been shown that a sequence as short as a tripeptide possesses, on average, the ideal number of non-carbon atoms required to maximise ligand-receptor interactions to develop drug-like molecules.…”
Section: Introductionmentioning
confidence: 99%
“…(5) The present synthetic approach is not only the first example of a metal-free C–N bond cleavage reaction for intermolecular peptide bond formation but also the most economical convergent peptide synthesis. (6) DKPs can be easily prepared according to known methods 16 b ,31 and are recognised to have unique bioactivities. 32 In addition, they are also attracting attention as new functional ingredients in foods and beverages.…”
Section: Discussionmentioning
confidence: 99%